2002
DOI: 10.1128/aem.68.2.728-737.2002
|View full text |Cite
|
Sign up to set email alerts
|

Listeria monocytogenes LO28: Surface Physicochemical Properties and Ability To Form Biofilms at Different Temperatures and Growth Phases

Abstract: The surface physicochemical properties of Listeria monocytogenes LO28 under different conditions (temperature and growth phase) were determined by use of microelectrophoresis and microbial adhesion to solvents. The effect of these parameters on adhesion and biofilm formation by L. monocytogenes LO28 on hydrophilic (stainless steel) and hydrophobic (polytetrafluoroethylene [PTFE]) surfaces was assessed. The bacterial cells were always negatively charged and possessed hydrophilic surface properties, which were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
175
3
20

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 290 publications
(222 citation statements)
references
References 37 publications
(32 reference statements)
22
175
3
20
Order By: Relevance
“…Chavant et al (28) reported that L. monocytogenes forms biofilms more rapidly on hydrophilic surfaces than on hydrophobic surfaces, compared to other typical microorganisms, probably due to interactions between the cell surface and environmental surfaces that enable cells to overcome repulsive forces and attach irreversibly (29). Hydrophilic surfaces are common in the food preparation environment, and contamination and subsequent adherence of pathogens to surfaces can occur if a good cleaning procedure is not practiced (30).…”
Section: Resultsmentioning
confidence: 99%
“…Chavant et al (28) reported that L. monocytogenes forms biofilms more rapidly on hydrophilic surfaces than on hydrophobic surfaces, compared to other typical microorganisms, probably due to interactions between the cell surface and environmental surfaces that enable cells to overcome repulsive forces and attach irreversibly (29). Hydrophilic surfaces are common in the food preparation environment, and contamination and subsequent adherence of pathogens to surfaces can occur if a good cleaning procedure is not practiced (30).…”
Section: Resultsmentioning
confidence: 99%
“…2,8 O termo biofilme não inclui somente os micro-organismos, mas também engloba o material extracelular produzido na superfície e qualquer material que esteja dentro da matriz resultante. [9][10][11] O termo biofilme se refere à interação dinâmica entre as populações bacterianas compostas por uma ou mais espécies, caracterizadas por heterogeneidades temporais (desenvolvimento), espaciais (organização espacial), funcionais (variação na atividade metabólica), estrutura hierárquica e estágios evolucionários bem definidos. Em geral, a diferença entre a simples adesão do micro-organismo às superfícies e o biofilme pode ser definida através dos seguintes critérios: o papel da superfície no crescimento da população bacteriana e a existência de comunicação célula-a-célula (quorum sensing) dentro da população.…”
Section: Biofilmesunclassified
“…A temperatura e a fase de crescimento podem influenciar sobre a composição da parede celular, tornando-a menos ou mais hidrofóbica, doadora ou aceptora de elétrons. 9 Todas as características físico-químicas são estritamente relacionadas com a adesão microbiana e a formação de biofilmes, e a alteração de cada parâmetro pode influenciar positiva ou negativamente sobre a adesão microbiana. 26 O desenvolvimento microbiano na superfície está associado com agitações massivas, reguladas pela cinética de crescimento celular e a quantidade de nutrientes disponíveis.…”
Section: 10unclassified
“…Incubation temperature may also affect cell surface properties, such as charge, hydrophobicity, and electron donor and acceptor characteristics (Briandet et al, 1999). For example, in Staphylococcus aureus and Listeria monocytogenes, cell surface hydrophobicity level increases with temperature, leading to a higher biofilm formation (Chavant et al, 2002;Di Ciccio et al, 2015). Additionally, temperature could change microbial transcriptomic profile: flagellin is generally repressed at temperatures above 30 °C in L. monocytogenes (Way et al, 2004).…”
Section: Temperaturementioning
confidence: 99%
“…For example, presence of Staphylococcus xylosus and Pseudomonas fragi, or bacteriocin-producing Lactococcus lactis reduced biofilm formation by L. monocytogenes (Van Houdt and Michiels, 2010). (Mariani et al, 2011;Wirtanen et al, 1996) Hydrophobicity Hydrophobic material surfaces favor attachment of bacteria with hydrophobic properties (An and Friedman, 1998;Katsikogianni and Missirlis, 2004) Surface charge Opposite surface charges of substratum and cell favor attachment (Morisaki and Tabuchi, 2009) Temperature a) Lower temperatures lead to more uniform properties of polysaccharides, which stimulate biofilm formation b) Lower temperatures decrease cell surface hydrophobicity level, leading to a lower biofilm formation (Chavant et al, 2002;Di Ciccio et al, 2015;Garrett et al, 2008) Oxygen concentration Decrease of oxygen within biofilms reduces bacterial metabolic activity and inhibits bacterial growth …”
Section: Microbial Interactionsmentioning
confidence: 99%